Literasi Keuangan Syariah, Inklusi Digital, dan Kinerja UMKM Halal melalui Orientasi Kewirausahaan - Abdi Rivaldi (Jaanur Elbarik Indonesia, 2026)
This study aims to examine the effects of Islamic financial literacy and digital financial inclusion on the performance of halal micro, small, and medium enterprises (MSMEs), with Islamic entrepreneurial orientation serving as a mediating variable. A quantitative explanatory research design was employed. Data were collected through questionnaire surveys administered to halal MSME owners in Indonesia using a purposive sampling technique. The proposed research model was analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM) to assess both direct and indirect relationships among the constructs. The findings are expected to demonstrate that Islamic financial literacy and digital financial inclusion positively influence Islamic entrepreneurial orientation, which subsequently enhances halal MSME performance. Furthermore, Islamic entrepreneurial orientation is expected to mediate the relationships between Islamic financial literacy, digital financial inclusion, and halal MSME performance.